Abolition and After the Paper Box Wages Council - Bright, David (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Abolition and After the Paper Box Wages Council," by C. Craig, Jill Rubery, Roger Tarling & Frank Wilkinson.